FAULTLESS SYSTEMS: YES WE CAN! - Abrial, Jean-Raymond (Computer (00189162), 2009)
The article discusses the need for gradual global improvements in software and system development. The entry notes that a definitions and requirements document must first be established before starting system development, while a modeling of the future system will help to instruct developers and engineers on how to explain and formalize their observations of the computerized system. It mentions that modelling also requires a process of simulation and proving through discrete transition systems.